2008
DOI: 10.1111/j.1573-7861.2008.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Are They Really Mama’s Boys/Daddy’s Girls? The Negotiation of Adulthood upon Returning to the Parental Home

Abstract: This article explores how living with parents affects the ways emerging adults construct their self-identity. Data are from in-depth interviews with 30 young adults who returned to live with their origin family after a period of residential autonomy. Respondents perceive adulthood as a psychological state, attained through a process of assuming responsibility for one's actions and learning how to interact with other adults (particularly parents) from a position of equality. Nonetheless, an economic component r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 57 publications
1
103
1
5
Order By: Relevance
“…Mitchell 1998)). While Sassler et al (2008) reported conflict between parents and children over the standards to which tasks had to be performed, which was also identified by the mother highlighted for group (ii). Several parents in group (iiia) expressed their negative feelings in developmental terms, referring to the behaviour of their offspring as 'immature'.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitchell 1998)). While Sassler et al (2008) reported conflict between parents and children over the standards to which tasks had to be performed, which was also identified by the mother highlighted for group (ii). Several parents in group (iiia) expressed their negative feelings in developmental terms, referring to the behaviour of their offspring as 'immature'.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the Pew Research Centre's telephone survey of a nationally representative US sample of 1625 adults aged 18-34, found that the 18-24 year olds were more positive than older co-resident children about the effects of co-residence on their relationship with parents (Parker 2012). Using qualitative data, Sassler et al (2008) found that almost three-quarters of their sample of 30 young adult 'returners' in Southern New England were positive about their experiences.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Sassler et al (2008) found that less than a third of their sample of 30 young adults in Southern New England living in the parental home, made financial contributions to the household, whether by paying rent or sharing in household expenditures; respondents often reported that parents did not ask them to contribute and some resisted making contributions. Survey data have revealed that nearly half of young American adults (aged 25 to 34 years) who were living with their parents, or had moved back in temporarily in recent years, paid rent (Parker, 2012).…”
Section: Financial Support By Parents and Financial Contributions By mentioning
confidence: 99%